Analisis Senyawa Ekstrak Metanol dan Fraksi N-Heksan Buah Parijoto (Medinilla Speciosa Blume) - ismah, kadar (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
The Muria Mountains in Kudus have the parijoto plant, which is renowned for its benefits passed down through generations. The extract of parijoto fruit (Medinilla speciosa Blume) contains secondary metabolite compounds such as alkaloids, polyphenols, quinones, saponins, glycosides, flavonoids, and tannins. Phytochemical screening using GC-MS instruments to determine the content of secondary metabolites and provide an overview of the compounds contained in parijoto fruit. The methanol extract test contains polyphenol compounds, quinones, saponins, flavonoids, tannins, and glycosides. Meanwhile, the n-hexane fraction contains quinone and polyphenol.